KOMPARASI KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI DENGAN KETERAMPILAN MENULIS TEKS CERITA FANTASI SISWA KELAS VII SMP NEGERI 22 PADANG - Hasibuan, Rosita; Hafrison, Mhd. (Universitas Negeri Padang, 2020)
ABSTRACTThe purpose of this research was to describe things as follow. First, it describes the writing skills of the report text of observations of grade VII junior high school 22 Padang. Secondly, it describes the writing skills of fantasy text for VII grade students of junior high school 22 Padang. Third, analyze the comparasion between the writing skills of the observation report text and the fantasy story writing skills of the seventh grade student. This type of research is quantitative research with descriptive analysis. Based on the result of the study, the following three things were concluded. First, the writing skills of the report text of observations of grade VII students of junior high school are in good qualifications (82,82). Secondly, the skills to write fantasy text for seventh grade student of junior high school 22 Padang are in good qualifications (80,66). Third, there is a significant difference between the writing skills of observations report text and the fantasy story writing skills of grade VII students of junior high school 22 Padang, so it can be concluded that H0 is rejected and H1 is accepted because the test results prove that the count is greater then the table 11,25>1,68.Â Kata Kunci: Komparasi, Menulis Teks LHO,Menulis Teks Cerita Fantasi